2001
DOI: 10.1046/j.1442-200x.2001.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between birthweight and body mass index at 3 years of age

Abstract: Infants with higher birthweight and/or greater weight gain during the first month of life may have a risk of being overweight at 3 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
2
32
0
7
Order By: Relevance
“…14,15,17,19,20,27,[33][34][35][36] Two studies reported associations that were not statistically significant, although they did not provide adjusted estimates. 37,38 No study reported less adiposity. A recent study evaluated children at age 7 with DXA scanning, and reported substantially higher over all body fat, but not truncal distribution of fat, and to a lesser extent higher lean body mass, in children exposed to prenatal smoking.…”
Section: Resultsmentioning
confidence: 99%
“…14,15,17,19,20,27,[33][34][35][36] Two studies reported associations that were not statistically significant, although they did not provide adjusted estimates. 37,38 No study reported less adiposity. A recent study evaluated children at age 7 with DXA scanning, and reported substantially higher over all body fat, but not truncal distribution of fat, and to a lesser extent higher lean body mass, in children exposed to prenatal smoking.…”
Section: Resultsmentioning
confidence: 99%
“…Our data are in agreement with other studies. 7-10 Tanaka et al 7 reported that there is a positive association between birth weight and BMI at 3 years of age in Japan. A case-control study by Takahashi and colleagues 8 suggested that children who were obese at 3 years of age had higher birth weights compared with their normal weight counterparts.…”
Section: Macrosomia and High Weight-for-height Z Yu Et Almentioning
confidence: 99%
“…[7][8][9][10] A rapidly increased rate of newborn macrosomia (birth weight X4000 g) has been documented since last two decades. For instant, In Yantai, China, the percentages of newborn macrosomia increased from 2.6% in the 1970s to 13.2% in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Há evidências na literatura sobre a associação do peso ao nascer com o estado nutricional, avaliado através do índice de massa corporal, em pré-escolares, 50 assim como uma forte e independente associação entre crianças com grande peso ao nascer e o sobrepeso e obesidade na infância. 51 Para Reilly et al, 52 um aumento em cada 100 g do peso ao nascer é um fator de risco relacionado à obesidade na infância apresentando associação independente e linear com uma maior prevalência de obesidade aos sete anos.…”
Section: Peso Ao Nascer E Medidas Corporaisunclassified
“…50 Em crianças não amamentadas, observa-se que quanto maior o incremento de peso por mês nos primeiros quatro meses de vida, maior a associação com o sobrepeso na idade escolar. 57 Já em adultos, segundo Stettler et al, 11 após avaliarem o crescimento infantil em sete ocasiões diferentes, o sobrepeso esteve associado ao ganho em 100 g no peso na primeira semana de vida.…”
Section: Rápido Crescimento Ponderal E Medidas Corporaisunclassified